Defining the Role of piRNAs in Testicular Cancer - Zyoud, Ahmad (2021)
Germ cell development and function are controlled by epigenetic modifications which regulate patterns of gene transcription throughout cell differentiation (Mazo, García-López and Weber 2014). Small non-coding RNAs play an essential role in germ cell development. PIWI interacting RNAs (piRNAs) are a type of small non-coding RNAs that have a critical role in germline maintenance, by silencing transposable elements and facilitating both transcriptional and post-transcriptional regulation. Recent studies have indicated the aberrant expression of specific piRNAs in various type of cancers, however, their function in testicular cancer remains unknown. Therefore, the current study aimed to investigate the expression of piRNAs in testicular cancer as well as their role in regulating expression by transposable elements-derived long non-coding RNAs. Herein, the piRNA transcriptome was analysed by bioinformatics analysis of Testicular Germ Cell Tumours (TGCT) deep sequencing data from The Cancer Genome Atlas (TCGA) in comparison to normal testis samples. Further, piRNAs-transposable element targets that generate antisense long non-coding RNAs transcripts were selected. This selection was done in order to elucidate its role in testicular cancer development and tumorigenesis. As a result, a piRNA signature was identified within the TGCTs and normal testis tissue indicating a role for piRNA in testicular cancer tumorigenesis. A differential and unique piRNA expression signature was also found in TGCTs subtypes, suggesting a specific function of piRNA subsets in the development of different types on TGCTs. Additionally, this study demonstrated the transcriptional regulatory role of piR-hsa-7221 in seminomas TGCTs. Indeed, piR-hsa-7221 was identified to regulate the expression of the long non-coding RNA (lncRNA) CASC9 by controlling the activation of the overlapping LINE-1 sequence. This regulation resulted by antisense interaction between piR-hsa-7221 and LINE-1 in cooperation with PIWIL2 and PIWIL4 proteins, thus controlling the expression of the antisense LINE-1generated transcript CASC9. Therefore, the described mechanism advances the understanding of piRNAs transcriptional regulation for the control of transposable elements and the critical role of PIWI proteins in piRNA guidance. Importantly, the identification of piR-hsa-7221 and its lncRNA target CASC9 highlights two novel genes that might play a critical role in testicular cancer development and therefore could represent promising biomarkers for the detection and targeted treatment of seminoma TGCTs.